2009
DOI: 10.1214/07-aos573
|View full text |Cite
|
Sign up to set email alerts
|

Gaussian model selection with an unknown variance

Abstract: Let $Y$ be a Gaussian vector whose components are independent with a common unknown variance. We consider the problem of estimating the mean $\mu$ of $Y$ by model selection. More precisely, we start with a collection $\mathcal{S}=\{S_m,m\in\mathcal{M}\}$ of linear subspaces of $\mathbb{R}^n$ and associate to each of these the least-squares estimator of $\mu$ on $S_m$. Then, we use a data driven penalized criterion in order to select one estimator among these. Our first objective is to analyze the performance o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
112
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(116 citation statements)
references
References 30 publications
4
112
0
Order By: Relevance
“…Lebarbier (2005) proposed c 1 = 5 and c 2 = 2 for optimizing the penalty (2) in the context of change-point detection. Penalties similar to (2) have been introduced independently by other authors (Rissanen 1983;Abramovich et al 2006;Barron et al 1999;Tibshirani and Knight 1999;Baraud et al 2009) and are shown to provide satisfactory results. Nevertheless, all these results about exponential collections assume that data are homoscedastic.…”
Section: Model Selectionmentioning
confidence: 97%
See 2 more Smart Citations
“…Lebarbier (2005) proposed c 1 = 5 and c 2 = 2 for optimizing the penalty (2) in the context of change-point detection. Penalties similar to (2) have been introduced independently by other authors (Rissanen 1983;Abramovich et al 2006;Barron et al 1999;Tibshirani and Knight 1999;Baraud et al 2009) and are shown to provide satisfactory results. Nevertheless, all these results about exponential collections assume that data are homoscedastic.…”
Section: Model Selectionmentioning
confidence: 97%
“…BGH In the context of Gaussian regression, Baraud et al (2009) propose a new penalized criterion, which does not depend on the a priori knowledge of the variance of the noise: The selected model results from the minimization over m ∈ M n of the criterion crit BGH (m)…”
Section: Alternative Competing Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…We also remark here that Baraud, Giraud, and Huet (2009) study BIC along with FPE, AIC, and AMDL. However they do not study the procedures as multiple testing procedures.…”
Section: Introductionmentioning
confidence: 93%
“…Alternative approaches to this problem also exist such as the model selection approach of (Baraud et al 2008) where a penalty criterion is introduced dependent upon the number of coefficients estimated as non-zero; or the work of (Beran 2004) where the penalized least squares (PLS) estimator are represented as hybrid shrinkage estimators.…”
mentioning
confidence: 99%